(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The aim of this study is to detect the prevalence and diagnosis of molecular characteristics of Cryptosporidium infection in handlers of domestic pigeons in Baghdad City. Traditional and molecular diagnostic methods were employed to detect and identify Cryptosporidium species. Materials and methods: Sixty stool samples were collected from the handlers of domestic pigeons, and various techniques, including direct smear, flotation concentration, staining methods, and DNA extraction coupled with nested polymerase chain reaction (PCR), were utilized. Results: The results obtained from traditional methods indicated an overall infection rate of 55% in handlers of domestic pigeons, while significant variations were noted between male and female handlers. Age group 21–40 years were found to have higher infection rates were found to have higher infection rates. The prevalence of Cryptosporidium also displayed temporal variability throughout the study period. Molecular analysis using nested PCR revealed higher infection rates of 86% in handlers of domestic pigeon samples. Genotyping and phylogenetic analysis identified the presence of Cryptosporidium parvam species in handlers of domestic pigeons, indicating zoonotic transmission potential. Conclusion: These findings underscore the high prevalence of Cryptosporidium infection among handlers of domestic pigeons in Baghdad City. J. Adv. Vet. Anim. Res., 10(4): 744–750, December 2023 http://doi.org/10.5455/javar.2023.j730